Assessing Life Balance and Work Addiction in High‐Pressure, High‐Demand Careers. (9th September 2019) - Reiner, Summer M.; Balkin, Richard S.; Gotham, Kerry R.; Hunter, Quentin; Juhnke, Gerald A.; Davis, R. J.
Abstract : Life balance is indicative of creating and sustaining a meaningful and satisfying quality of living. Contrarily, work addiction is overinvesting in work‐related behaviors, thereby truncating important life‐balance domains. Given a growing body of literature specific to life balance and the increasing incidence of work addiction and burnout among professionals, the authors evaluated life balance and work addiction among 409 professionals in high‐pressure, high‐demand careers. A strong relationship between life‐balance domains and the propensity toward work addiction was noted. Specifically, stress/anxiety and sleep disturbances were identified as work addiction indicators reducing perceptions of life balance. Counselors should assess these critical domains with clients working in high‐pressure, high‐demand careers and be prepared to support these professionals as they restructure their lives to improve life‐balance domains.